The use of scaffolding and interactive learning strategies in online courses for working nurses: implications for adult and online education - Salyers, Vince; Carter, Lorraine; Cairns, Steve; Durrer, Luke (My University, 2014)
This paper reviews the foundational literature of contemporary e-learning, with a focus on scaffolding, instructional design, and engagement. These concepts are then considered in two limited case studies, each involving e-learning and adult learners—in particular, nurse-learners. The first case study describes the use of a scaffolding model called Introduction, Connect, Apply, Reflect, and Extend (ICARE) in e-learning for nursing education. The second is a reflection on the use of engagement strategies for the purposes of discourse and learning in a different online nursing context. Because nursing educators were among the early adopters of e-learning, they are important mentors to others who are adopting e-learning strategies at this time. Additionally, the paper is a crossroads publication: it reminds the reader of the imperative to review theory and emerging evidence related to e-learning and to bring key findings to the actual practice of e-learning in order to benefit the adult student. This commitment to theory and practice will enable the evolution of e-learning for all learners, including returning adult learners and working professionals.
Keywords: scaffolding; instructional design; interaction; best practices; engagement; adult education; e-learning